Neanderthals, trees and dental calculus: new evidence from El Sidrón. (April 2016) - Radini, Anita; Buckley, Stephen; Rosas, Antonio; Estalrrich, Almudena; de la Rasilla, Marco; Hardy, Karen
Abstract: Abstract : Analysis of dental calculus is increasingly important in archaeology, although the focus has hitherto been on dietary reconstruction. Non-edible material has, however, recently been extracted from the dental calculus of a Neanderthal population from the 49 000-year-old site of El Sidrón, Spain, in the form of fibre and chemical compounds that indicate conifer wood. Associated dental wear confirms that the teeth were being used for non-dietary activities. These results highlight the importance of dental calculus as a source of wider biographical information, and demonstrate the need to include associated data within research, in particular tooth wear, to maximise this valuable resource.